2015
DOI: 10.1007/s00299-015-1738-4
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a new class of blue-fluorescent lipid droplet markers for live-cell imaging in plants

Abstract: Abstract:Key message: The present work demonstrates the use and advantages of novel, live cell permeable, Lipid droplet localizing, non toxic, blue fluorochromes for use in live plant cells. Abstract:Lipid droplets (LDs) are ubiquitous components of both animal and plant cells. They consist of a core of neutral lipids surrounded by a monolayer of phospholipids, glycolipids and/or sterols with embedded amphipathic proteins. Although initially considered to be simple energy depots, they have recently emerged as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…31 In order to complete the available palette of color, blue emitting LDs markers have recently been reported. 37,38,39,40 Although they showed good selectivity and despite an example where two-photon excitation was used, 35 their brightness in imaging are quite limited due to their UV shifted excitation spectra and quite low molar absorption coefficients, thus leading to low excitation efficiency using the common 405 nm laser. Except one example where a near infrared fluorophores served to visualize the most viscous LDs, 41 LDs probes being able to report their environment such as composition or polarity using fluorescence imaging have not yet been reported.…”
mentioning
confidence: 99%
“…31 In order to complete the available palette of color, blue emitting LDs markers have recently been reported. 37,38,39,40 Although they showed good selectivity and despite an example where two-photon excitation was used, 35 their brightness in imaging are quite limited due to their UV shifted excitation spectra and quite low molar absorption coefficients, thus leading to low excitation efficiency using the common 405 nm laser. Except one example where a near infrared fluorophores served to visualize the most viscous LDs, 41 LDs probes being able to report their environment such as composition or polarity using fluorescence imaging have not yet been reported.…”
mentioning
confidence: 99%
“…For the Nile red staining, 4 μL of stock solution (500 μg mL -1 dissolved in acetone) was added to 1 mL of 75% glycerol, some droplets were added on a glass slide containing air-dried sections, a coverslip was placed and observed immediately with a LSM 510 META confocal microscope; the fluorophore was excited with a 488 and 514 nm laser lines and emission was filtered with a BP 575–615 IR filter ( Kuntam et al, 2015 ).…”
Section: Methodsmentioning
confidence: 99%
“…Cytoplasmic LD can be stained in vivo with different dyes. We compared the commonly used Nile red (James et al, 2010;McLachlan et al, 2016) to LD540 (Spandl et al, 2009), and the recently described blue-fluorescent LD dyes for live-cell imaging in plant (Kuntam et al, 2015). We found that LD540 perfectly co-localized with the well characterized LD marker ERG6-RFP in yeast with little or no staining of non-LD structures ( Figure S2).…”
Section: Attspo Can Modulate the Level Of Cytoplasmic Ld In Arabidopsismentioning
confidence: 99%